Prospects for the Myanmar rubber sector: An analysis of the viability of smallholder production in Mon State - van Asselt, Joanna; Htoo, Kyan; Dorosh, Paul A. (International Food Policy Research Institute, 2017)
As a result of recent political reforms, Myanmar has the opportunity to enact major policy changes to reinvigorate its agriculture sector. In this context, Myanmar’s rubber sector has the potential to become an even greater source of export earnings and rural household incomes, but there are major challenges related to low rubber productivity and poor rubber quality. Using data from the Mon State Rural Household Survey (MSRHS) conducted from May to June 2015, as well as qualitative data collected from rubber producer focus groups and other interviews with rubber producers, traders, and processors, this paper describes the cost structure of rubber production in Mon State. We then estimate smallholder production costs and the profitability of smallholder rubber production under various alternative yield and price scenarios. The results suggest that if the weaknesses hindering the profitability of the rubber sector are not addressed, the rubber sector will likely stagnate. Moreover, in the absence of a major increase in world prices (substantially above the 2000–2016 average), new rubber investments will not be profitable without major improvements in yield and quality. Further, increasing only yields or only quality, or only improving the institutional environment, will not result in positive returns on investment for smallholders; reforms are needed in all three areas. If these weaknesses are addressed, however, Myanmar’s new investments will be profitable and Myanmar could become an important rubber producer and exporter on the world stage.